Feasibility Study Implementation of Commercial Type Photovoltaic System on Prospective Buildings in UTHM Pagoh - Eddie Syafzainizam, Erin Eriana; Baharom, Md Nor Ramdon (Progress in Engineering Application and Technology, 2024)
Solar energy, radiation from the Sun capable of producing heat, causing chemical reactions, or generating electricity. Photovoltaic (PV) panels, sometimes referred to as solar panels, are devices that use the photovoltaic effect to turn sunlight into energy. The study is mainly to profile the electrical load and to plan photovoltaic system implementation at Block B. SOLCAST and ETAP were used to do PV system simulation. The results help decision-makers assess whether a commercial photovoltaic system is feasible and should be installed as a renewable energy source for the Block B of  UTHM Pagoh.